FRAGMENTS OF MADURA WOMEN IN THE WORKS OF MADURESE AND EASTERN JAVANESE LITERATURE: A READING OF ECOFEMINISM - Siswanto Siswanto; Sukatman Sukatman; Akhmad Taufiq; Endang Sri Widayati; Anita Widjajanti; Fitri Nura Murti (Prosiding Seminar Nasional dan Internasional HISKI, 2021)
This paper will present the fragments or dimensions of Madurese women in the context of environmental relations with culture, social interaction and gender in the works of Madurese and East Javanese writers. The focus of this research study is the narratives of Madurese women in viewing and interpreting the relationship between nature or the environment with Madurese culture, whether influenced by environmental changes, social dynamics, local wisdom, Madurese community norms in literary works written by Madurese writers. and East Java. The approach in this study is ecofeminism as a formal object aimed at uncovering the relationship between women and the environment inherent in Madurese Man and his entire culture. The interpretive descriptive method is used to analyze and interpret data from material objects, including prose and poetry by Madurese and East Java writers which have been determined based on the research objectives.